(untitled) (International Journal of Ayurveda and Pharma Research, 2018)
Burn injury has been associated with the evolution of human civilization since time immemorial. Burn injuries has always been faced by human in different era with change of mode injury from past to present. Unlike other diseases the basics of burn injury remains more or less same. The basic concepts and principles of management of burn injury is described in Ayurveda are very much relevant and useful in this era of modern surgery. Sushrut Samhita, the treasure of surgical knowledge of ancient Indian civilization, is a rich source of information regarding burn injury, assessment and management. Most of the other scholars of Ayurveda follow the basic concept of Sushrut Samhita. All the Brihatrayee (three greater treatises) and Laghu trayee (three lesser treatises) and other relevant textbooks of Ayurveda studied to search the different data regarding Dagdha vrana (burn injury), etiological description, gradation, different principles of treatment and available dressing material. The collected data evaluated scientifically to make it usable in the modern era of surgery. The result shows that although there is change in mode of burn injury found in modern era, the basic principles of etiology, classification, management and use of dressing material are almost the same as standard burn wound management of contemporary medical science. So the benefits of Ayurveda can be inducted in modern era of burn care.